Description of Paenibacillus dokdonensis sp. nov., a new bacterium isolated from soil. Issue 3 (17th March 2021) - Paek, Jayoung; Bai, Lu; Shin, Yeseul; Kim, Hongik; Kook, Joong-Ki; Chang, Young-Hyo
Abstract : Two strains isolated from soil samples were designated as YH-JAE5 T and YH-JAE2. The isolates were facultative anaerobic, Gram-stain-variable, motile, rod-shaped bacteria. Phylogenetic analysis indicated that the isolates belonged to the genus Paenibacillus, but the 16S rRNA gene sequence similarities were <98 % when compared with other species within the genus. Analysis of rpoB gene revealed the isolates formed a sub-cluster with P. chibensis . The only menaquinone identified was MK-7. The two isolates contained meso -diaminopimelic acid within their cell wall peptidoglycan. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phospholipid, aminophospholipids, and lipids. The major fatty acids were C15 : 0 anteiso and C15 : 0 iso. The average nucleotide identity, average amino acid identity, and digital DNA–DNA hybridization values between isolate YH-JAE5 T and the most closely related reference strain ( Paenibacillus chibensis KCTC 3758 T ) were 81.7, 84.8 and 23.4 %, respectively. The G+C content of the genomic DNA was 47.4 mol%. Thus, the polyphasic data revealed that YH-JAE2 (=KCTC 43239=JCM 34435) and YH-JAE5 T (=KCTC 43059=JCM 33533) represent a new species. The name Paenibacillus dokdonensis sp. nov. is proposed.